A Digital Services Act és az EU fogyasztóvédelmi joga (The Digital Services Act and the consumer protection law of the EU) - András Tóth (KözigazgatásTudomány)
More than twenty years have passed since the first EU legislation regulating online services was adopted. In that time, this sector has developed and changed enormously. This process has led to the need for regulatory reforms, one of which is the Digital Services Act (DSA). This paper describes the reasoning behind the DSA and the regulatory objectives that led the EU legislators to adopt it. After a general overview, the detailed consumer protection rules of the DSA are presented, where two major topics are discussed. The first topic is the DSA’s due diligence requirements arising from the special responsibilities, including the rules of ranking and promoting the legality of online advertising. The second topic covers consumer protection provisions for the own services of online platforms and is also divided into two parts, targeted advertising and dark patterns. The study is not limited to a presentation of the DSA rules, the specific parts of other EU legislation and their differentiation are also presented where relevant.